b-Jet identification in the D0 experiment - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; et al. (Elsevier B.V., 2010)
Algorithms distinguishing jets originating from b quarks from other jet flavors are important tools in the physics program of the D0 experiment at the Fermilab Tevatron p (p) over bar collider. This article describes the methods that have been used to identify b-quark jets, exploiting in particular the long lifetimes of b-flavored hadrons, and the calibration of the performance of these algorithms based on collider data. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: b-Jet identification; b-Tagging; D0; Tevatron; Collider